PENGEMBANGAN LKS MATEMATIKA SD MENGGUNAKAN PENDEKATAN SAINTIFIK - Muhammad Saufi (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Teachers have difficulty in learning due to the inactivity of students so that the Minimum Completeness Criteria (KKM) have not been achieved. One of the reasons for not achieving the KKM is the absence of other teaching materials such as worksheets that students use in understanding the material. Students Work Sheet (LKS) is a printed teaching material in the form of paper sheets containing material, summaries and instructions dor implementing kearning tasks that must be done by students, which refers to the basic competencies that must be achieved. The purpose of this research is to produce math worksheets using a scientific approach that is valid and pratical. The type of research used is research and development (R&D). The method of developing math worksheets based on a scientific approach used 4D development research steps developed by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. This step consists of 4 stages, namly: Define, Design, Develop, and Disseminate, whose application is tailored to the needs of the researcher. Data collection technique used is quantitative and qualitative analysis. The results of the study were obtained based on the validator assessment consisting of 2 lecturers and 1 teacher that the feasibility of SD mathematics worksheets using a scientific approach received a validation value that was very valid. Based on data processing on the value of the student response questionnaire results, SD mathematics worksheets using a scientific approach are very practical to be used by students.